Bacteroides thetaiotaomicron-derived outer membrane vesicles promote regulatory dendritic cell responses in health but not in inflammatory bowel disease - Lydia Durant; Régis Stentz; Alistair Noble; Johanne Brooks; Nadezhda Gicheva; Durga Reddi; Matthew J. O’Connor; Lesley Hoyles; Anne L. McCartney; Ripple Man; E. Tobias Pring; Stella Dilke; et al. (Microbiome, 2020)
Abstract Background Bacteroides thetaiotaomicron (Bt) is a prominent member of the human intestinal microbiota that, like all gram-negative bacteria, naturally generates nanosized outer membrane vesicles (OMVs) which bud off from the cell surface. Importantly, OMVs can cross the intestinal epithelial barrier to mediate microbe-host cell crosstalk involving both epithelial and immune cells to help maintain intestinal homeostasis. Here, we have examined the interaction between Bt OMVs and blood or colonic mucosa-derived dendritic cells (DC) from healthy individuals and patients with Crohn’s disease (CD) or ulcerative colitis (UC). Results In healthy individuals, Bt OMVs stimulated significant (p < 0.05) IL-10 expression by colonic DC, whereas in peripheral blood-derived DC they also stimulated significant (p < 0.001 and p < 0.01, respectively) expression of IL-6 and the activation marker CD80. Conversely, in UC Bt OMVs were unable to elicit IL-10 expression by colonic DC. There were also reduced numbers of CD103+ DC in the colon of both UC and CD patients compared to controls, supporting a loss of regulatory DC in both diseases. Furthermore, in CD and UC, Bt OMVs elicited a significantly lower proportion of DC which expressed IL-10 (p < 0.01 and p < 0.001, respectively) in blood compared to controls. These alterations in DC responses to Bt OMVs were seen in patients with inactive disease, and thus are indicative of intrinsic defects in immune responses to this commensal in inflammatory bowel disease (IBD). Conclusions Overall, our findings suggest a key role for OMVs generated by the commensal gut bacterium Bt in directing a balanced immune response to constituents of the microbiota locally and systemically during health which is altered in IBD patients. Video Abstract